Purwarupa Sistem Pemantauan Lingkungan Rel Kereta Api berbasis Jaringan Sensor Nirkabel dalam Lingkup Persinyalan Kereta Api Blok Bergerak - Cakra Bhirawa; Rakhmadhany Primananda; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The writer research is focused on the topic of moving block signalling system in the railways system. Where this system is proposed to be applied outside of an urban city or a sterilized railways network from it's surrounding. The writer intended to enhanced the already existing research based on the RFID which can provided the necessary information for tracking the position of a train and at the same time calculate the speed of that train so it can be sent to the control center with MQTT protocol. The prototype of this control center itself is designed to be a MQTT broker and scaled down system of the operation control center (OCC). The control center can receive information about the surrounding railway tracks environment with the wayside unit which has been designed to sense an object with an infrared sensor and detecting the vibration of the train by using an accelerometer sensor. This research can provide a prospect for an integrated sensing system about it surrounding environments to be implemented in the signalling aspect of a train. Because the main reason that the moving block signalling system can't be implemented in the rural or suburban area is due to the railway tracks is still intersect with the main road or doesn't have a wall to limit the activities in the tracks area. After finishing this research, the writer can conclude that this prototype of moving block signalling system can be implemented in a smaller scale with a delay around 0.4 - 1.1 second for each received and sended information by the system in the same 802.11 network and access point. This value can provide a glimpse to scale this research in the near future so it can be adjusted to each perspective railway tracks environment.